SDN/NFV‐based handover management approach for ultradense 5G mobile networks. (23rd October 2018) - Gharsallah, Amina; Zarai, Faouzi; Neji, Mahmoud
Summary: With the great increase of connected devices and new types of applications, mobile networks are witnessing exponential growth of traffic volume. To meet emerging requirements, it is widely agreed that the fifth‐generation mobile network will be ultradense and heterogeneous. However, the deployment of a high number of small cells in such networks poses challenges for the mobility management, including frequent, undesired, and ping‐pong handovers, not to mention issues related to increased delay and failure of the handover process. The adoption of software‐defined networking (SDN) and network function virtualization (NFV) technologies into 5G networks offers a new way to address the above‐mentioned challenges. These technologies offer tools and mechanisms to make networks flexible, programmable, and more manageable. The SDN has global network control ability so that various functions such as the handover control can be implemented in the SDN architecture to manage the handover efficiently. In this article, we propose a Software‐Defined Handover (SDHO) solution to optimize the handover in future 5G networks. In particular, we design a Software‐Defined Handover Management Engine (SDHME) to handle the handover control mechanism in 5G ultradense networks. The SDHME is defined in the application plane of the SDN architecture, executed by the control plane to orchestrate the data plane. Simulation results demonstrate that, compared with the conventional LTE handover strategy, the proposed approach significantly reduces the handover failure ratio and handover delay. Abstract : We propose a Software‐Defined Handover Management Engine (SDHME) to optimize the handover control mechanism in 5G ultradense networks based on SDN/NFV technologies. In particular, we have proposed an approach capable to determine the best handover planning for mobile node (MN) based on the QoS requirements of the application, state of the MN, and network conditions provided by the control plane. Simulation results demonstrate that, compared with the existing work, the proposed approach significantly reduces the handover failure ratio and handover delay.